The use of the health belief model to assess predictors of intent to receive the COVID-19 vaccine and willingness to pay - Wong, Li Ping; Alias, Haridah; Wong, Pooi-Fong; Lee, Hai Yen; AbuBakar, Sazaly (Human vaccines & immunotherapeutics, 2020)
The development of a vaccine against SARS-CoV-2 infection is on the way. To prepare for public availability, the acceptability of a hypothetical COVID-19 vaccine and willingness to pay (WTP) were assessed to provide insights into future demand forecasts and pricing considerations. A cross-sectional survey was conducted from 3 to 12 April 2020. The health belief model (HBM) was used to assess predictors of the intent to receive the vaccine and the WTP. A total of 1,159 complete responses was received. The majority reported a definite intent to receive the vaccine (48.2%), followed by a probable intent (29.8%) and a possible intent (16.3%). Both items under the perceived benefits construct in the HBM, namely believe the vaccination decreases the chance of infection (OR = 2.51, 95% CI 1.19-5.26) and the vaccination makes them feel less worry (OR = 2.19, 95% CI 1.03-4.65), were found to have the highest significant odds of a definite intention to take the vaccine. The mean ± standard deviation (SD) for the amount that participants were willing to pay for a dose of COVID-19 vaccine was MYR$134.0 (SD±79.2) [US$30.66 ± 18.12]. Most of the participants were willing to pay an amount of MYR$100 [US$23] (28.9%) and MYR$50 [US$11.5] (27.2%) for the vaccine. The higher marginal WTP for the vaccine was influenced by no affordability barriers as well as by socio-economic factors, such as higher education levels, professional and managerial occupations and higher incomes. The findings demonstrate the utility of HBM constructs in understanding COVID-19 vaccination intention and WTP.